MLX plays a key role in lipid and glucose metabolism in humans: evidence from in vitro and in vivo studies - Nagarajan, SR; Livingstone, EJ; Monfeuga, T; Lewis, LC; Ali, SHL; Chandran, A; Neville, MJ; Dearlove, DJ; Chen, L; Maroteau, C; Ruby, MA; Hodson, L (Elsevier, 2023)
Background and aim Enhanced hepatic de novo lipogenesis (DNL) has been proposed as an underlying mechanism for the development of NAFLD and insulin resistance. Max-like protein factor X (MLX) acts as a heterodimer binding partner for glucose sensing transcription factors and inhibition of MLX or downstream targets has been shown to alleviate intrahepatic triglyceride (IHTG) accumulation in mice. However, its effect on insulin sensitivity remains unclear. As human data is lacking, the aim of the present work was to investigate the role of MLX in regulating lipid and glucose metabolism in primary human hepatocytes (PHH) and in healthy participants with and without MLX polymorphisms.